Optimising the cost-effectiveness of risk-based screening for diabetic retinopathy - Sampson, Christopher James (2020)
Publicly provided health screening programmes tend to offer standardised screening for a fixed eligible population. Recently, the development of risk calculation engines has introduced the potential for the stratification of screening based on individuals' risks of disease onset. This possibility raises practical, methodological, and ethical challenges. To date, no such programme has been the subject of an economic evaluation. In this thesis we present reason and basis for the allocation of screening based on individual risk.